Novel M2 -selective, Gi -biased agonists of muscarinic acetylcholine receptors - Randáková, Alena; Nelic, Dominik; Ungerová, Dana; Nwokoye, Peter; Su, Qiwen; Doležal, Vladimír; El-Fakahany, Esam E; Boulos, John; Jakubík, Jan (British journal of pharmacology, 2020)
BACKGROUND AND PURPOSE: More than 30% of currently marketed medications act via GPCRs. Thus, GPCRs represent one of the most important pharmacotherapeutic targets. In contrast to traditional agonists activating multiple signalling pathways, agonists activating a single signalling pathway represent a new generation of drugs with increased specificity and fewer adverse effects. EXPERIMENTAL APPROACH: We have synthesized novel agonists of muscarinic ACh receptors and tested their binding and function (on levels of cAMP and inositol phosphates) in CHO cells expressing individual subtypes of muscarinic receptors, primary cultures of rat aortic smooth muscle cells and suspensions of digested native tissues from rats. Binding of the novel compounds to M2 receptors was modelled in silico. KEY RESULTS: Two of the tested new compounds (1-(thiophen-2-ylmethyl)-3,6-dihydro-2H-pyridinium and 1-methyl-1-(thiophen-2-ylmethyl)-3,6-dihydro-2H-pyridinium) only inhibited cAMP synthesis in CHO cells, primary cultures, and native tissues, with selectivity for M2 muscarinic receptors and displaying bias towards the Gi signalling pathway at all subtypes of muscarinic receptors. Molecular modelling revealed interactions with the orthosteric binding site in a way specific for a given agonist followed by agonist-specific changes in the conformation of the receptor. CONCLUSIONS AND IMPLICATIONS: The identified compounds may serve as lead structures in the search for novel non-steroidal and non-opioid analgesics acting via M2 and M4 muscarinic receptors with reduced side effects associated with activation of the phospholipase C signalling pathway.
Keywords: Animals; Muscarinic Agonists; agonisté muskarinových receptorů; křečci praví; Muscarinic Antagonists; CHO buňky; receptory muskarinové; signální transdukce; antagonisté muskarinových receptorů; Signal Transduction; Cricetulus; Receptor, Muscarinic M2; Receptors, Muscarinic; receptor muskarinový M2; krysa rodu Rattus; zvířata; Rats; Cricetinae; CHO Cells